PREDIKSI akurat ! Soal-soal UN yang akan keluar SMP/MTs 2015 Dewi Paramita Sari ..[etal]; penyunting Muji Lestari - Dewi Paramita Sari; Muji Lestari (Planet Ilmu, 2014)
vii, 443 hlm : ilus.; 26 cm +CD